Hubungan Citra Tubuh, Pengetahuan dan Konsumsi Tablet Tambah Darah (Fe) dengan Anemia Remaja - Anggun Cahyati; Ajib Jayadi; Hidayatusy Syukrina Puteri (Jurnal Kebidanan dan Keperawatan Medika, 2026)
One of the nutritional problems commonly experienced during adolescence is anemia. Anemia is a decrease in the quantity of red blood cells in circulation or the amount of haemoglobin being below the normal limits. The aim of this research is to determine the relationship between body image, knowledge, and the consumption of iron supplement tablets with the incidence of anemia in adolescent girls in the Working Area of Sidorejo Community Health Centre, Sekampung Udik District, East Lampung Regency in 2025. Quantitative research type with an analytical survey using a cross-sectional approach. The research was conducted in the work area of the Sidorejo Health Centre, Sekampung Udik District, East Lampung Regency in May-June 2025. The entire population consisted of female adolescents, with a sample of 84 female adolescents. The sampling technique used was cluster random sampling. Statistical testing used the Chi-square test. The frequency distribution of anaemia was 49 (58.3%), non-anaemia 35 (41.7%). The frequency distribution of body image was good 39 (46.4%), poor body image 45 (53.6%). The frequency distribution of knowledge was good 33 (39.3%), sufficient knowledge 24 (28.6%), poor knowledge 27 (32.1%). The frequency distribution of iron supplement tablet consumption was good 36 (42.9%), poor iron supplement tablet consumption 48 (57.1%). The p-value result was 0.000 < α (0.05) indicating a relationship between body image and the incidence of anaemia in adolescent girls. The p-value of 0.000 < α (0.05) shows a relationship between knowledge and the incidence of anaemia in adolescent girls, and the p-value of 0.044 < α (0.05) means there is a relationship between iron tablet consumption (Fe) and the incidence of anaemia in adolescent girls in the Working Area of Sidorejo Health Centre, Sekampung Udik District, East Lampung Regency in 2025.